Validation of low-volume blood collection tubes for routine hematologic testing: Blood tube filling and hematologic testing - Lippi, Giuseppe; Martini, Loredana; Cortivo, Barbara; Zecchetto, Chiara; Ferrari, Anna (Journal of Medical Biochemistry, 2024)
Background: Low-volume blood tubes offer several advantages in facilitating blood collection, reducing iatrogenic anemia and spurious hemolysis, but their clinical reliability must be validated. We planned this investigation for establishing the reliability of routine hematologic testing in low-volume tubes before their implementation into clinical practice.Methods: Blood was drawn from 44 ostensibly healthy laboratory professionals into three blood tubes, as follows: 3.0 mL of blood into a 3.0 mL K2EDTA standard blood tube, 0.5 mL of blood into a second 3.0 mL K2EDTA standard blood tube, and 0.5 mL of blood into a 0.25-0.5 mL K2EDTA low-volume blood tube. Hematologic testing was performed on Sysmex XN-10 hematology analyzer.Results: Statistically significant differences were observed in total white blood cell count, neutrophil count, lymphocyte count, red blood cell count, platelet count, hemoglobin, hematocrit, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), and mean platelet volume in both 0.5 mL-filled 3.0 mL standard blood tubes as well as in the 0.5 mL-filled low-volume blood tubes. Although none of these variations was found to be clinically significant in the 0.5 mL-filled low-volume blood tube compared to the desirable specifications, hematocrit, MCV and MCHC displayed a clinically significant bias in the 0.5 mL- filled 3.0 mL K2EDTA standard blood tube.Conclusions: These results suggests that K2EDTA low-volume blood tubes could safely replace standard blood tubes for preventing the receipt of insufficient samples, but also for facilitating blood collection in patients with difficult veins and reducing the risk of iatrogenic anemia and spurious hemolysis.